A full layered numerical model for predicting hysteretic behavior of unbonded flexible pipes considering initial contact pressure. (June 2021) - Wang, Lidong; Yue, Qianjin
Abstract: This paper presents a method to predict the bending hysteretic behavior of unbonded flexible pipes using full layered numerical general finite element models with an implicit solver. A predefined stress fields method is proposed to simulate the initial contact pressure effect introduced by the fabrication process. Detailed finite element modeling techniques are illustrated based on system balance principles of a cantilever beam system. The models can capture the interactions (normal contact and tangential friction behavior) between and among layers adequately, thus giving reasonable stress predictions of tensile armor tendons in both longitudinal and transverse (radial and lateral) directions. The results show that the proposed method through prescribing a fixed initial hoop stress value in the outer sheath could give consistent bending moment-curvature relations for all test pressure levels and corresponding numerical results. The stress-curvature relations reveal that the tensile armor tendons slide in an interval between the loxodromic and geodesic curves as proved in the open literature. In addition, sensitivity studies including element types, boundary conditions, material properties, normal contact stiffness and friction coefficients are performed to validate the feasibility of the proposed models. Moreover, if plastic layers are modeled by solid elements, the friction moment will be larger than that of using shell elements due to Poisson's effect on pipe elongation.